Informação para o monitoramento da convenção da convenção dos direitos da criança: a atuação da rede NGO Group - Paula Gomes Quintao (2008)
The present article focus its attention on NGO Group for CRC web, an ONGs group that leads to support the Children Rights Convention (CRC) introduction on countries where this document has been ratified. CRC has been approved by UNO in 1989 and received uncountable number of ratifications never seen before. Altogether there are 191 embercountries,meanwhile theres the obligation for each country introduce the rights subscribed by CRC and report this process. Understanding what is the web spreading, whether is a tool which supports a bigger interaction among the members; how has civil society loaded this files in order to act toward transnational sites alongside this global transition; how exactly how far the web produces information and this is put available. All these is what is expected.